2018
DOI: 10.1186/s12978-018-0500-0
|View full text |Cite
|
Sign up to set email alerts
|

Why ethnicity and gender matters for fertility intention among married young people: a baseline evaluation from a gender transformative intervention in rural India

Abstract: BackgroundSocial inequities in early child bearing persist among young married people, especially among tribal populations in India. Rural women belonging to tribal groups and those coming from poor households are more likely to give birth before age 18. This paper explores the connection between ethnicity, gender and early fertility intention among young married people in rural India.MethodsThe data is drawn from a cross sectional baseline evaluation of an intervention programme in rural India. A sample of 27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 12 publications
0
9
0
1
Order By: Relevance
“…The primary reason for low contraceptive use may be the low access to contraceptive knowledge and services as observed in Maharashtra and Tamil Nadu 21 24. Other reasons could be early marriage, childbearing observed among tribal groups in Madhya Pradesh and Rajasthan25 which was in turn associated with low contraceptive use11 and lower education 24. Other studies in central India and Nepal substantiated the role of women and husbands’ education, age of women and number of surviving boys in the use of any modern method of contraception 5 26.…”
Section: Discussionmentioning
confidence: 99%
“…The primary reason for low contraceptive use may be the low access to contraceptive knowledge and services as observed in Maharashtra and Tamil Nadu 21 24. Other reasons could be early marriage, childbearing observed among tribal groups in Madhya Pradesh and Rajasthan25 which was in turn associated with low contraceptive use11 and lower education 24. Other studies in central India and Nepal substantiated the role of women and husbands’ education, age of women and number of surviving boys in the use of any modern method of contraception 5 26.…”
Section: Discussionmentioning
confidence: 99%
“…The findings are similar to what Walia et al, in their study conducted in a rural area of North India, concluded about men's participation and dominance in reproductive decision making (Walia et al, 2021). The social norms and role-stereotyping of genders have been documented similarly by researchers in India and abroad, emphasizing tribal and disadvantaged populations (Khanna et al, 2018;Willan et al, 2020). Keynejad et al reported their young respondents' perception of gender-based violence being a major cause for concern (Keynejad et al, 2018).…”
Section: What Is Already Known and What This Study Addsmentioning
confidence: 84%
“…There is an ongoing fear of side effects and health issues associated with the use of different SARC and LARC methods (17). Additionally, research on contraceptive use in India suggests that familial pressure, as well as gender and social norms, play a strong role and that these norms have shifted little over time (17)(18)(19). Many women do not use contraception following marriage in order to demonstrate their fertility, and as a result of pressure from husbands, in-laws and communities (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%